Strategi Pendidikan Karakter di Era Media Sosial (Asosiasi Mahasiswa Program Pascasarjana | Institut Agama Islam Darussalam | IAID | Ciamis | Jawa Barat, 2022)
This article aims to explore character education strategies in the social media era. This study is considered important because the era of social media really has a serious effect on children's character. This study uses the literature review method, in which the researcher reviews books, journal articles, proceedings of relevant scientific activities, then analyzes them before writing them down in the text of this scientific article. The results of the study show that character is essentially formed when it is habituated and repeated. With regard to character education strategies, character education can be applied to all subjects. Every subject related to norms needs to be developed and related to everyday life. In this era of social media, the role of family, teachers and society is very important in improving children's character. The family as the main and first place for students to live their lives needs to supervise and guide children in a loving, firm and careful manner. In this era of social media, the teacher's role in building the character of students will be increasingly difficult and complex. Teachers not only teach good character, but also how to direct students to implement noble character in everyday life. As a role model, the teacher must apply good character to himself.